Educação ambiental como subsídio à gestão ambiental: uma proposta para a bacia hidrográfica do rio Marrecas - SO / PR - Rosa, Marcela Dozolina da (2016)
The current research aims to analyse the municipal and state public policy inserted on hydrographic basin of river Marrecas, especially those related to environmental education and conservation of water resources. The management process proposed is grounded in National Policy (Law 9.433/1997) and State (Law 12.726/1999) of the Water Resources that integrate the hydrographic basin as territorial unity of action in order to manage water resources in a decentralized manner, with the participation of public authorities, users and the community. Therefore, will be discussed the possibility of implementing an inter-municipal consortium to provide a planning of nature conservation activities between the municipalities of Flor da Serra do Sul, Francisco Beltrão e Marmeleiro to the integrated management of natural resources, primordially the water resources. This insertion is justified by the fact to list a space cut in the current proposal management pertinent to the committee of the tributaries of Baixo Iguaçu, that encompasses more than seventy municipalities, covering a considerably large area to boost the conservation and maintenance of water resources of thos territory. Must be observed that the delimination proposed does not relieve the legitimacy of the committee, but allow autonomy for that the three municipalities develop projects to raise founds that will assist in the management brought, well as the promotion of the integration of the population of more incisive way in this process. In this context, the environmental education is presented as a mechanism to coordinate the construction and integration of the concomitants environmental projects to insertion of subjects in the course of the consortium s proposition. Of Besides the suggestion of the insertion of this form of integrated management is being analyzed the collection and implantation of resources accruing from payment for environmental services, Ecological ICMS, with the aim the maintenance of public supply fountains, or units of conservation through payment for environmental services by the State Government of Paraná to the municipalities. At the same step, were researched the laws and others materials that would integrate the Municipal Master Plans and the Water Resources Plans in order to identify the forms of use and occupation of land, plus the direction of territorial planning, with emphasis on the use of water. To better understand the applicability of the instruments and laws, were interviewed six farmers from the aforementioneds municipalities, from with was found incompatibility between the program established by the municipalities and their execution, especially regarding the performing of works formation and environmental education.